Interaction between influenza and tuberculosis in South Africa, a country with high prevalence of tuberculosis and HIV - Walaza Sibongile (My University, 2018)
BACKGROUND For both influenza disease and tuberculosis disease, the lungs are the main site of pathology and HIV is an important risk factor for severe illness. There are limited published data on the interaction between tuberculosis disease and influenza disease. OBJECTIVES We aimed to assess the effect of influenza and tuberculosis coinfections on clinical presentation, progression of illness and disease outcome; and to evaluate the burden of excess mortality associated with influenza infection in patients with tuberculosis disease. METHODS A systematic review of published literature on the interaction between influenza and tuberculosis disease was conducted. Using surveillance data, we estimated the burden of tuberculosis disease among patients hospitalized with severe respiratory illness (SRI) and assessed the risk of influenza and tuberculosis coinfection on in-hospital mortality. For SRI patients we included HIV infection status in our models when this information was available. Ecological models were used to estimate excess influenza-associated mortality among individuals with tuberculosis disease compared to non tuberculosis respiratory deaths. RESULTS The systematic review revealed paucity and poor quality of available literature on the interaction between influenza and tuberculosis disease. Experimental animal studies suggested that influenza tuberculosis coinfection resulted in more severe outcomes than a single infection. Whereas the majority of the analytical studies ( 4/5) showed no association. Analysis of surveillance data revealed that the prevalence of tuberculosis among patients hospitalized with SRI was 28% (593/2097); 18% ( 133/729) among patients with symptoms duration: S:14 days. Among patients with symptom duration ?: of .7 days, patients coinfected with tuberculosis and influenza as compared to patients with tuberculosis only were at increased risk of death (aRRR 5.5, 95% CI l.2-25 .3). In a separate analysis, laboratory confirmed tuberculosis disease was associated with an increased risk of death in hospitalized patients who tested positive for the influenza virus (aOR 4.5, 95% CI 1.5-13.3), and laboratory-confirmed influenza virus infection was associated with an increased risk of death in hospitalized patients who tested positive for tuberculosis (aOR 2.3, 95% CI 1.02-5.2). In individuals <65 years, the risk of influenza-associated mortality was greater among pulmonary tuberculosis deaths irrespective of HIV status compared to HIV-infected non-tuberculosis respiratory deaths (relative risk (RR): 5.2; 95% Cl: 4.6-5.9 and HIV-uninfected (RR: 61.0; CI: 41.4-91.0) non tuberculosis respiratory deaths. CONCLUSION Tuberculosis was common in patients hospitalized with SRI, including among individuals with a duration of symptoms 􀀝of 14 days. Tuberculosis and influenza coinfection compared to single tuberculosis or influenza infection was associated with an increased risk of mortality. These data support recommendations for patients with tuberculosis disease to be prioritized for influenza vaccination.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy